The Emotional Regulation and School Readiness in Preschool Children: Regulasi Emosi dan Kesiapan Sekolah pada Anak-Anak Prasekolah - Fitriana Salsabilla Firdaus; Widyastuti Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: School readiness represents a multidimensional set of foundational competencies required for successful transition from preschool to formal education, encompassing cognitive, social, physical, and emotional domains. Specific Background: Emotional maturity—particularly emotional regulation—has been identified as a core component of children’s ability to adapt to academic demands, interpersonal interactions, and classroom routines at the elementary level. Knowledge Gap: Prior studies have broadly examined emotional development, yet limited research has focused specifically on emotional regulation as a distinct construct associated with school readiness among preschool children. Aims: This study aimed to determine whether a statistically significant positive relationship exists between emotional regulation and school readiness in preschool children aged 5–6 years in Sidoarjo. Results: Using a quantitative non-experimental correlational approach with a cross-sectional design and Pearson product-moment analysis, the findings indicated a significant positive correlation between emotional regulation and school readiness (r = 0.288; p = 0.006), with emotional regulation accounting for 8.3% of the variance in readiness scores. Novelty: The research isolates emotional regulation—rather than broad emotional development—as the focal predictor, employing validated standardized instruments adapted to the Indonesian context. Implications: These findings suggest that emotional self-management skills constitute an important internal factor associated with children’s preparedness for formal schooling, while also highlighting the presence of additional internal and external determinants that warrant further investigation. Highlights: A statistically significant positive association was identified between children’s ability to manage emotions and preparedness for entering formal schooling. The measured predictor accounted for a modest proportion of variance, indicating substantial contribution from other unexamined factors. Most participants were categorized at moderate levels across both assessed constructs, reflecting typical developmental patterns in the sampled population. Keywords: Emotional Regulation; School Readiness; Preschool Children; Social Emotional Development; Early Childhood Education